FEATURES OF PROFESSIONAL TRAINING OF FUTURE ECONOMISTS-INTERNATIONAL: Array - Berveno, O.; Stadnyk, G. (Municipal economy of cities. Series: «Economy science», 2020)
In today's world issues of educational quality are becoming increasingly important. Today the quality of training is determined by its readiness for effective professional activity, the ability to adapt to rapidly changing and uncertain conditions of the modern world, professional skills, as well as the ability to use the acquired knowledge in solving professional problems. In modern research on the peculiarities of training specialists for future employment, considerable attention is paid to various aspects of economic education. The process of continuous improvement of professional training of higher education seekers requires a constant search for new tools, methods and tools to improve the educational process, and, accordingly, research on this issue. The purpose of the article is to analyze the features, trends, competencies and new tools in preparing future international economists for effective work. The four main areas of employment of international economists include: international institutions and organizations; international corporations and other structures of international business; domestic business structures; public authorities and public institutions. In the modern period, the competence approach is the most important factor in ensuring the quality of higher education. Competences are formed comprehensively, in the process of all forms and activities of the applicant. Innovative education involves its focus on obtaining innovative skills of applicants, which involves their gradual involvement in research, project development and more. Dissemination of the results of the fourth industrial revolution ("Industry 4.0") and the emergence of an era of innovation, when advanced technologies radically change entire sectors of the economy and society as a whole, requires skills to apply these technologies in various fields of international economics. The peculiarity of the analyzed educational program "International Economy" is the focus on the requirements and needs of the urban labor market, the needs of the urban economy through constant interaction with stakeholders.